Assessment of post-excitatory long-interval cortical inhibition in adult attention-deficit/hyperactivity disorder - Retz, Wolgang; González-Trejo, Ernesto; Römer, Konstanze D.; Philipp-Wiegmann, Florence; Reinert, Philip; Boureghda, Samir S T; Strauss, Daniel J.; Low, Yin Fen (D. Steinkopff-Verlag, 2012)
In order to further examine cortical impairment in adult ADHD patients and to test the hypothesis of a disturbed neuronal inhibition in adults with ADHD, late auditory evoked potentials were measured. By using paired-chirp auditory late responses, we compared 15 adults with ADHD with 15 control subjects, focusing on the inhibition elicited by the stimuli. Besides amplitude measurements, a time-frequency phase coherence study using the wavelet phase synchronization stability (WPSS) was performed. ADHD was diagnosed according to DSM-IV criteria. All ADHD subjects were without medication and did not suffer from any further axis I disorder. WPSS analysis revealed impaired auditory inhibition for ADHD patients for interstimulus intervals (ISI) between 500 and 1,100 ms as compared with healthy controls. By analyzing the WPSS in the interval from 80 ms to 220 ms, mean inhibition of the test chirp was found to be 6% in the ADHD group and 38.5% in the control subjects (p = 0.01). Moreover, overall smaller amplitudes in the N100 and P200 waves at all ISI were found (p = 0.04 and p = 0.02). However, reproducibility indices in the amplitude measurements were low, thus supporting the use of the instantaneous phase-based analysis method. The results support the hypothesis of reduced intracortical inhibition as a correlate of disturbed brain function in adults with ADHD. © 2012 Springer-Verlag.